Pembrolizumab for the Treatment of Locally Advanced Cutaneous Squamous Cell Carcinoma: Patient Selection and Special Considerations - Stewart M; Geiger JL (Cancer Management and Research)
Matthew Stewart,1 Jessica L Geiger2 1Department of Internal Medicine, Primary Care Institute, Cleveland Clinic Foundation, Cleveland, OH, USA; 2Department of Hematology and Medical Oncology, Taussig Cancer Institute, Cleveland Clinic Foundation, Cleveland, OH, USACorrespondence: Matthew Stewart, Department of Internal Medicine, Primary Care Institute Cleveland Clinic Foundation, Cleveland, OH, USA, Email stewarm7@ccf.org Jessica L Geiger, Department of Hematology and Medical Oncology, Taussig Cancer Institute Cleveland Clinic Foundation, Cleveland, OH, USA, Email geigerj@ccf.orgAbstract: The treatment of locally advanced cutaneous squamous cell carcinoma (cSCC) has shifted with the advent of immune checkpoint inhibitors (ICIs). Traditional treatment methods have been met with limited efficacy and durability. Recently, ICIs such as pembrolizumab and cemiplimab have emerged as effective alternatives for treating advanced cSCC. Pembrolizumab, approved by the FDA in 2020 for recurrent or metastatic cSCC not amenable to curative surgery or radiation, has shown promising results in clinical trials. Immunotherapy is also being explored in neoadjuvant settings, with ongoing trials evaluating its potential to improve outcomes for high-risk patients with recurrent or metastatic disease. However, patient selection remains crucial, with the tumor microenvironment playing a key role in predicting treatment response. With many patients achieving a complete response, immunotherapy presents a promising option; however, ongoing research is needed to refine its use, especially in immunocompromised or high-risk patients.Keywords: cutaneous squamous cell carcinoma, cSCC, immunotherapy, pembrolizumab